2021
DOI: 10.1080/20008198.2021.1920201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trimethylamine N-oxide (TMAO) as a potential biomarker of severe stress in patients vulnerable to posttraumatic stress disorder (PTSD) after acute myocardial infarction

Abstract: Background : Posttraumatic stress disorder (PTSD) is a frequently observed stress-related disorder after acute myocardial infarction (AMI) and it is characterized by numerous symptoms, such as flashbacks, intrusions and anxiety, as well as uncontrollable thoughts and feelings related to the trauma. Biological correlates of severe stress might contribute to identifying PTSD-vulnerable patients at an early stage. Objective : Aims of the study were (1) to determine whether blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“… 23 Both TMA and its metabolites are presumed to play a pivotal role in microbiotic pathways relating to the gut–brain axis and have been linked to several psychiatric and neurologic diseases. 24 26 However, TMA has also been found to lead to the development of arteriosclerosis and cardiovascular disease. 27 Through the gut microbiome, TMA is synthesized from choline found in eggs, red meat or fish and is subsequently transformed in the liver into its active metabolite trimethylamine N oxide (TMAO), 28 which eventually acts as a neuronal protein stabilizer.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Both TMA and its metabolites are presumed to play a pivotal role in microbiotic pathways relating to the gut–brain axis and have been linked to several psychiatric and neurologic diseases. 24 26 However, TMA has also been found to lead to the development of arteriosclerosis and cardiovascular disease. 27 Through the gut microbiome, TMA is synthesized from choline found in eggs, red meat or fish and is subsequently transformed in the liver into its active metabolite trimethylamine N oxide (TMAO), 28 which eventually acts as a neuronal protein stabilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that AMI patients suffer from severe and prolonged stress [ 35 ]. Prolonged AMI-related stress and the concomitant activation of proinflammatory cytokines make AMI patients more vulnerable to depression [ 11 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…After AMI, many patients suffer from severe and prolonged stress [ 35 ], which is associated with neuroinflammation and vulnerability to depression. In particular, IL-6 plays an important role in the inflammatory hypothesis of depression.…”
Section: Objectivesmentioning
confidence: 99%
“…TMAO is predictive of adverse cardiovascular events, including myocardial infarction (Tang et al, 2013[ 22 ]; Baranyi et al, 2021[ 3 ]). A dose-response meta-analysis by Schiattarella et al (2017[ 21 ]), based on seven studies, also showed that the relative risk (RR) for all-cause mortality significantly increases by 7.6 % per 10 μmol/L increment of TMAO [summary RR: 1.07, 95 % CI (1.04-1.11)] (Schiattarella et al, 2017[ 21 ]).…”
Section: Discussionmentioning
confidence: 99%